World Bank Support to Aging Countries : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2021)
Population aging—resulting from falling fertility rates, declining mortality, and increased longevity—shapes the profile and the needs of a growing number of countries. How effective has the World Bank been in tailoring its support to provide an adequate response to this evolving challenge? This evaluation is the first report from the Independent Evaluation Group to assess the World Bank’s contribution to diagnosing client countries’ demographic issues related to population aging; understanding the variance in policy needs and context specificities; and providing vision, tools, and resources to respond to challenges in countries at different stages of aging. This evaluation aims to inform the World Bank Group’s Board of Executive Directors, management, and staff about the relevance, coherence, and operationalization of World Bank support to aging countries. The World Bank is increasingly called on to offer support to respond to the deep socioeconomic challenges its clients are facing because of population aging. Providing adequate responses to aging countries will become more of a priority as the phenomenon accelerates and becomes more prominent in World Bank client countries.